Wellspring of magic - Fields, Jan.; Durney, Ryan. (Berne, IN Annie's Attic, 2007)
When six ordinary girls accidentally open a secret door into another world, it doesn't take long for adventure, and danger, to find them.
Keywords: Fantasy; Princesses -- Fiction; Magic -- Fiction; Princesses -- Juvenile fiction; Magic -- Juvenile fiction; Fantasy; Adventure stories